Unusual Presentation of Lemierre's Syndrome Due to Fusobacterium nucleatum - Williams, Michael D. (American Society for Microbiology, 2003)
We report a case of Lemierre's syndrome due to Fusobacterium nucleatum in a previously healthy 19-year-old male. This is the first case report of Lemierre's syndrome due to thrombophlebitis of the external jugular vein. The patient had a rapid clinical response to anticoagulation and antibiotics, as supported by anecdotal evidence.